Synaptotagmin-1 and -7 Are Redundantly Essential for Maintaining the Capacity of the Readily-Releasable Pool of Synaptic Vesicles - Bacaj, Taulant; Wu, Dick; Burré, Jacqueline; Malenka, Robert C.; Liu, Xinran; Südhof, Thomas C. (PLOS Biology, 2015)
Synaptotagmins function not only as calcium sensors in triggering synaptic vesicle fusion but also contribute to the preparation of synaptic vesicles for fusion, being required for full priming of vesicles ready for subsequent triggering of exocytosis.